AKTIVITAS ANTIJAMUR EKSTRAK ETANOL DAUN KRATOM (Mitragyna speciosa) TERHADAP JAMUR Microsporum canis - Susanto, Dhessy; Natalia, Diana; Widiyantoro, Ari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The world population experiencing dermatophytosis has reached 20%. Dermatophytosis is an infection caused by dermatophyte fungi. The prevalence in Asia reaches 35.6%. One of the fungi that causes dermatophytosis is Microsporum canis. Microsporum canis is known to be resistant to antifungal drugs. Kratom (Mitragyna speciosa) is a plant originating from Southeast Asia and in Indonesia it is often found in the Kapuas Hulu area, West Kalimantan. Kratom leaves are widely used as herbal medicine and have secondary metabolite compounds that have the potential to be used as antifungals. This study aims to determine the antifungal activity of ethanol extract of kratom leaves (Mitragyna speciosa) on the growth of Microsporum canis. Phytochemical screening was carried out using the Thin Layer Chromatography (TLC) scanner method and spray testing to determine the secondary metabolite compounds of the extract being tested. The test extract was made in concentrations of 5%, 10%, 15%, 20%, 25%, 50%, 75%, and 90% (w/v) with ethanol as a solvent. 8 µg itraconazole discs were used as a positive control and 10% DMSO was used as a negative control. Antifungal activity testing was carried out using the disc diffusion method by measuring the fungal growth inhibition zone. The ethanol extract of kratom leaves contains secondary metabolite compounds, namely alkaloids, terpenoids, steroids, flavonoids and tannins with the most dominant groups of alkaloid and tannin compounds. The results showed that there was no growth inhibition zone for Microsporum canis at all extract concentrations tested. The ethanol extract of kratom leaves does not have antifungal activity against the growth of Microsporum canis.